Diamond Devices for High Acuity Prosthetic Vision. Issue 1 (5th December 2016) - Ahnood, Arman; Meffin, Hamish; Garrett, David J.; Fox, Kate; Ganesan, Kumaravelu; Stacey, Alastair; Apollo, Nicholas V.; Wong, Yan T.; Lichter, Samantha G.; Kentler, William; Kavehei, Omid; Greferath, Ursula; et al.
Abstract : Retinal implants restore a sense of vision, for a growing number of users worldwide. Nevertheless, visual acuities provided by the current generation of devices are low. The quantity of information transferable to the retina using existing implant technologies is limited, far below receptor cells' capabilities. Many agree that increasing the information density deliverable by a retinal prosthesis requires devices with stimulation electrodes that are both dense and numerous. This work describes a new generation of retinal prostheses capable of upscaling the information density conveyable to the retina. Centered on engineered diamond materials, the implant is very well tolerated and long‐term stable in the eye's unique physiological environment and capable of delivering highly versatile stimulation waveforms – both key attributes in providing useful vision. Delivery of high‐density information, close to the retina with the flexibility to alter stimulation parameters in situ provides the best chance for success in providing high acuity prosthetic vision. Abstract : The design and testing of a diamond, biocompatible, hermetic, high‐density, scalable electrode array is described that can deliver high‐density electrical stimulation to the retina (shown in the included figure). The device provides an unprecedented level of flexibility in stimulation strategy and is an ideal platform to establish the limits of acuity achievable by electrical stimulation of the retina.